Letter (copy) - Citrine, Walter, 1887-1983
027-0058-001 International. WMC/WJB/AT/93. 10th October, 1939. M. Pascual Tomas, Depute 69, rue de Taur, Toulouse, France. Dear M. Tomas, Some time ago we received through the post a Money Order for the sum of £30. No letter accompanied it; the envelope contained nothing else. However, as we recognised your name on the Money Order we concluded that this was the amount you wished transferred in accordance with the wish expressed in your last letter. We duly communicated with the appropriate Authorities and steps have been taken to get the money delivered as arranged; but we think it necessary to inform you that owing to the regulations that have been made with regard to the exchange of money and the inevitable delays in communications to foreign countries, the transaction may take a longer time than than it would otherwise have done. In any case, you can be assured that the money is in safe hands and will eventually reach those to whom you wish it to be given. Yours faithfully, General Secretary. 292/946/27/58